Revisiting habits and heterogeneity in demands - Markus Fritsch; Andrew Adrian Yu Pua; Joachim Schnurbus (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2019)
We conduct a narrow replication of Browning and Collado (Journal of Applied Econometrics 2007; 22(3): 625-640). They estimate a linear panel AR(1) version of an Engel curve for six consumption composites using iterated GMM. We find that the coefficient estimates and standard errors differ from the reported results when we use their instrument set; in particular, we find habit formation in non-durable services and no state dependence in small durables. Despite finding evidence for weak instruments, our results support most of the claims made in the original paper and are also unable to detect intertemporal dependence strong enough to resolve existing macro puzzles.
Keywords: C23; C26; D12; 330; habit formation; linear dynamic panel data methods; weak instruments